Estudo do gasto energético de repouso e total em indivíduos com neurofibromatose Tipo 1 e sua correlação com força muscular, composição corporal e consumo alimentar - Marcio Leandro Ribeiro de Souza (2018)
Introduction: Neurofibromatosis type 1 (NF1) is a genetic disease, autosomal dominant, which is mainly characterized by neurocutaneous changes, but may also have multisystemic involvement. Although the clinical manifestations of NF1 are well documented, nutritional aspects have begun to be studied recently. A previous study with NF1 adults raised hypothesis of changes in total energy expenditure (TEE) and a possible relationship with food consumption and body composition. Objective: To study the resting energy expenditure (REE) and TEE in individuals with NF1 and their relationships with body composition, muscle strength and dietary intake. Methods: A sample of 26 individuals with NF1 (14 men and 12 women) aged 18-45 years old were compared to 26 control volunteers matched for age, sex, body mass index (BMI), and physical activity level. Weight, height and circumferences (arm and waist) were measured. Body composition was assessed by dual energy X-ray absorptiometry (DXA). The densitometry of the whole body, spine and femur also provided bone mass and bone mineral density (BMD) in these regions. REE and TEE were evaluated by indirect calorimetry. The muscle strength was evaluated by the handgrip test using a dynamometer, and calculated as maximum muscle strength (Fmax) and per unit area (Farea). Food intake were evaluated through one day 24hrecall and two days food records (three nonconsecutive days).The following diet constituents were investigated: energy, protein, lipid, cholesterol, carbohydrates, fiber, calcium, magnesium, manganese, phosphorus, iron, sodium, potassium, copper, zinc, thiamine, riboflavin, pyridoxine, niacin, vitamin C, vitamin D, vitamin A, and saturated, monounsaturated and polyunsaturated fatty acids, linoleic acid and linolenic acid. The body fat percentage were also evaluated by bioelectrical impedance and skinfolds thickness, and the results were compared to DXA (gold standard method). Predictive equations of REE and TEE were compared to indirect calorimetry, also considered the gold standard method for this evaluation. Results: The mean age was 34.31 ± 6.05 and 32.92 ± 6.14 years old in the NF1 and control groups, respectively (P=0.316). Stature was lower in individuals with NF1 (P=0.003). There were no differences in weight, BMI, waist circumference, fat mass, body fat percentage and body fat index. Appendicular lean mass adjusted by BMI was lower in the NF1 group (P=0.048). Bone mass was also lower in the NF1 group (P=0.046) as well as total body and spine BMD (P=0.036 and P=0.015, respectively). Individuals with NF1 also presented reduction of Fmax (P=0.035) and Farea (P=0.028). The adjusted REE by weight (P=0.046), lean mass (P=0.013) and appendicular lean mass (P=0.004) was higher, while the respiratory quotient (QR) (P=0.008) was lower in NF1. Individuals with NF1 oxidized more lipids and less carbohydrates than control group (P=0.011 and P=0.029, respectively). There were no differences in energy and macronutrients intake. Among micronutrients, individuals with NF1 consumed less calcium, iron and vitamin A, as well as consumed more sodium, polyunsaturated fatty acids and linoleic acid. In gender stratification, the observed changes in energy expenditure, body composition and muscle strength occurred only in women with NF1 compared to the control group. There was no difference in these aspects among men. The values of REE and TEE correlated negatively with body fat percentage, and positively with anthropometric variables (weight, height, BMI, waist circumference and body surface), with body composition variables (lean mass, appendicular lean mass), with the bone variables (bone mass and total body BMD), with the strength variables (Fmax and Farea). There was no correlation of REE and TEE with fat mass, body fat index and food intake variables (energy and macronutrients). Regression analysis showed that lean mass was the variable that most influenced REE in NF1. In the methods comparison, all predictive equations using skinfolds underestimated the percentage of fat in NF1 individuals, and only the equation of Sun and collaborators using the bioelectrical impedance approached more than the body fat percentage evaluated by DXA. All eight equations of REE underestimated this value compared to indirect calorimetry, and only the equation using 35kcal/kg/day approached the TEE of this study. Conclusions: Individuals with NF1 have an increased REE adjusted by weight or lean mass or appendicular lean mass compared to the control group. The NF1 group in this study have lower lean mass adjusted for BMI and lower maximal muscle strength, which may indicate early sarcopenia in this population. Women with NF1 respond differently to these changes. The results of this study allow us to conclude that individuals with NF1 present alterations in energy metabolism. The mechanisms of these changes in REE and the use of energy substrates, such as lipids and carbohydrates, need to be investigated in further studies.